Psychology of Religion: The Relationship Between Islamic Spirituality and Psychological Well-Being - Fera Firdausi Nuzula (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Psychological well-being is an indicator of individual well-being to meet the criteria for positive psychological functioning. One of the factors that can fulfill a positive psychological function is the presence of a high spirit of spirituality which is assisted by the ability to interpret life which cannot be separated, such as carrying out the values of truth and goodness to achieve prosperity. The aim of this research is to determine the relationship between spirituality and psychological well-being. Respondents in this study totaled 115 people consisting of 32 male and 83 female Muslim respondents with an age range of 18-25 years. In this study, the Ryff scale of psychological well-being and the Swinton scale of spirituality was used. The data collection method uses two scales, namely the spirituality scale and psychological well-being. Data were analyzed using Pearson's Product Moment correlation technique. The results show that the correlation between psychological well-being and Islamic spirituality is 0.528 with a significance value of 0.000. It is known that the correlation is classified as a fairly strong correlation, meaning that there is a fairly strong relationship between psychological well-being and Islamic spirituality. Keywords: relationship, psychological well-being, islamic spirituality